Studi in silico senyawa golongan flavonoid dari ranting dan akar dadap serep (Erythrina subumbrans) sebagai antipiretik - Montero, Mahkota Alda Mora; Wardani, Arief Kusuma (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Studies in silico offer an exciting world where researchers use the power of computing to explore a variety of scientific phenomena. In silico allows researchers to virtually test thousands of potential compounds, including natural ingredients, interacting with biological targets. This can speed up drug discovery and reduce reliance on expensive laboratory trials. Erythrina subumbrans is a plant in the Papilonaceae family that has been phytochemically tested to contain flavonoids suspected of having antipyretic effects. The study aims to identify the most potentially antipyretic compounds among the eight flavonoid groups of the branches and roots of Dadap Serep (Erythrina subumbrans). The study uses the molecular docking method. Tests were conducted against eight flavonoids of the branches and roots of the Dadap serep, namely pinocembrin, 3,6,4’-trichydroxyflavone, 3,6-dihydroxylflavon, lupalbigenin, erysubin F, genistein, 5-hydroxyphoronone, and abyssinone V, as well as positive controls of paracetamol against target proteins with PDB code 1CX2. The data analysis compared the total binding energy and hydrogen binding scores on the emerging amino acid residues. The test results showed that the three most potentially antipyretic compounds were lupalbigenin, erysubin F, and abyssinone V, with consecutive total bending energy scores of -126.3 kcal/mol, -113.1 kcal/mol, and -111.8 kcal/mol.